Association of the IRF6 rs2235371 and rs861019 Polymorphisms with Non-Syndromic Cleft Lip with or without Cleft Palate in the Yakut Population - Nadezhda I. Pavlova; Aleksandra T. Diakonova; Vladislav A. Alekseev; Lyubov S. Mironova; Vladimir V. Dodokhov; Khariton A. Kurtanov; Innokenty D. Ushnitsky (International Journal of Biomedicine, 2021)
Background: Non-syndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common birth defects. NSCL/P can be broadly divided into cleft lip only (CLO), cleft palate only (CPO), and cleft lip with cleft palate (CLP) based on clinical presentation. The aim of this study was to investigate the relationship between the IRF6 gene polymorphisms and non-syndromic cleft lip with or without cleft palate (NSCL/P) in the Yakut population. Methods and Results: In 23 OFC patients and 58 unrelated control subjects from the Yakut population, we tested two SNPs (rs2235371 and rs861019) with a minor allele frequency of more than 5% in the candidate gene IRF6. We found that the SNP marker rs861019 showed significant differences in allele frequencies (OR=2.07, 95%CI: 1.01–4.23, P=0.04) between the NSCL/P patients and the comparison group. Analysis of allele frequencies for rs861019 SNP in subgroups showed that there was a difference in the frequency between CLP and control (OR=5, 95% CI: 1.61-15.53, P=0.11); however, this result was not significant. Genotype analysis showed significant differences in patients from the CLP subgroup in comparison with controls for homozygous (AA compared with GG) (OR=9.00, 95% CI: 1.03–78.58, P=0.03), heterozygous (GA compared with GG) (OR=5.50, 95% CI: 1.05-28.75, P=0.04,), recessive (GG compared with GA + AA) (OR=6.67, 95% CI: 1.61-27.58; RR=4.78, 95% CI: 1.42–16.10, P=0.008,) and co-dominant (GG compared with GA, compared with AA) (P=0.02) inheritance models. Diplotype analysis showed that the NSCL/P group was more likely to have the [CC]-[GG] diplotype than the comparison group. This diplotype carries the risk GG genotype (rs861019) (30.4%) and does not carry the risk T allele(rs2235371). In the CLP subgroup, two diplotypes ([CT]-[GG] and [CC]-[GG]) were found more often than in the comparison group. Both diplotypes carry the risk GG genotype(rs861019; 33.3%). In the CPO subgroup, the [CT]-[GG] diplotype was more common. In the CLO subgroup, only two diplotypes ([CC]-[GA] and ...